Numerical simulations of liquids with amorphous boundary conditions - Cavagna, Andrea (2010)
It has recently become clear that simulations under amorphous boundary conditions (ABCs) can provide valuable information on the dynamics and thermodynamics of disordered systems with no obvious order parameter. In particular, they allow the detection of a correlation length that is not measurable with standard correlation functions. Here we explain what exactly is meant by ABCs, discuss their relation with point-to-set correlations and briefly describe some recent results obtained with this technique.